Energy and water balance studies in the boundary layer over Delhi (India) - DAS, Yashvant; PADMANABHAMURTY, Bamapati; MURTY, Aipillay Satya Narayana (Contributions to Geophysics and Geodesy, 2009)
This  paper  describes  the computation  of various  ﬂuxes  of energy  and  water balance  components in the boundary layer over Delhi, for the years 1997–98 and 1998–99. Bulk-aerodynamic method has been used for the computation of sensible heat (H ) and latent heat (LE) ﬂuxes.  Soil heat ﬂux (G) has been directly measured using heat ﬂux plate and  also estimated using  conductivity equation for comparison.  Book-keeping procedure of Thornthwaite’s has been used for water  balance  evaluation. Potential evapotranspiration  (PE)  is computed using  Thornthwaite’s  method  and  compared with  Penman’s  for the representative  station.  The  results  of the computed  ﬂuxes  of energy  and  water  balance  components were compared with  UREMBS-94 (Urban Rural  Energy  and  Moisture Balance  Studies - ES/63/018/84 – 1994) results  for both the winter and  summer  seasons for urban (dry)  and  rural  (moist) areas. It was found that there persists an energy imbalance in both the seasons for urban/dry as well as rural/moist areas.  However,  urban areas  showed  positive  (+V e) energy  imbalances  and  act  as heat/pollution  sources,  whereas  the rural/moist areas  showed  negative (−V e) energy  imbalances and  act  as  heat/pollution  sinks.    These  results  are  in  good agreement with  the UREMBS–94 results.  On the other hand,  water balance  analysis  for urban/dry and  rural/moist  areas  showed  the  same  ranges  of moisture  indices  indicating hardly any  shift  in climate.  However,  UREMBS–94 results  showed  climatic  shift  in the urban regions.